The impact of regulatory fines on shareholder returns - J. Strydom; M. Ward; C. Muller (South African Journal of Business Management, 2015)
Corruption has been shown to undermine the efficiency of market-based economies by allowing participants to profit from illegal rent-seeking activities, which decrease public support for business and increase the cost of capital (Zingales, 2015). Over the past decade, the Competition Commission in South Africa has investigated and Issued punitive fines amounting to around R8bn to companies engaged in non-competitive behaviour. Using event study methodology, we examine the impact on the share prices of listed companies upon the announcement of an investigation, a fine, and the payment of thefine. We find that shareholder returns were unaffected at the initiation and payment stages of the process, but that the returns were positively affected at the conviction stage. A buy-and-hold longitudinal study was also undertaken to determine if an ex-post portfolio consisting of stocks of convicted companies out-performed an equal-weighted all share benchmark, as well as a portfolio of matched companies which had not been fined. The results reveal that both the portfolio of fined companies and the matched portfolio of non-fined companies out-performed the market benchmark over a 24-year period. However, the portfolio consisting of convicted companies underperformed the portfolio of companies which had not been fined. We conclude that the market anticipated the fines and that the quantum of fines levied was less than expected. We also find that the non-competitive behaviour of convicted companies did not benefit their shareholders in the long-term.
Keywords: 650